Extratesticular gliomatosis peritonei after mesenteric teratoma: a case report and literature review. Issue 9 (September 2021) - Li, Jiaqiang; Li, Shoulin; Xiao, Dong; Song, Jiaming; Mao, Jianxiong; Yin, Jianchun
Mesenteric teratoma is a rare extragonadal teratoma. Gliomatosis peritonei (GP) is mature glial tissue implanted into the peritoneum's surface and is mainly accompanied by ovarian teratoma. Only a few cases of gliomatosis have occurred in the extraperitoneum. We present a rare case of a 3-year-old boy who presented with extratesticular GP after excision of an immature mesenteric teratoma at 2 months old. After the extratesticular mass was excised, we found ductile tissue on the surface of the terminal spermatic cord and epididymis. Some ductile tissue of the epididymis was removed and sent to a laboratory for a pathological examination. The mass and the ductile tissue of the epididymis had a hard consistency. The pathological diagnosis was extratesticular gliomatosis. Complete surgical resection of the teratoma and GP is helpful for identifying the presence of malignant lesions and for preventing malignant transformation. However, characteristics of GP lesions are extensive and they are difficult to completely remove. Moreover, GP is usually benign. Therefore, the residual GP tissue was not completely removed in our case. The child is still in good health, but requires lifelong follow-up. In conclusion, we report our experience of a rare case of extraperitoneal GP from an extragonadal teratoma.